Bibliometric Analysis with VOSviewer on Workplace Diversity and Its Implications for Organizational Practices - Wibisono, Yohanes; Sopiah, Sopiah; Zagladi, Arief Noviarakhman (Universitas Negeri Surabaya, 2025)
This study applies a bibliometric approach to evaluate publication trends related to